Functional Reconstitution of Dopamine D2 Receptor into a Supported Model Membrane in a Nanometric Confinement - Nagai, Rurika; Sugimachi, Ayane; Tanimoto, Yasushi; Suzuki, Kenichi G. N.; Hayashi, Fumio; Weikert, Dorothée; Gmeiner, Peter; Kasai, Rinshi S.; Morigaki, Kenichi (Advanced Biology, 2021)
Dopamine D2 receptor (D2R), a G-protein-coupled receptor (GPCR), plays critical roles in neural functions and represents the target for a wide variety of drugs used to treat neurological diseases. However, its fundamental physicochemical properties, such as dimerization and affinity to different lipid environments, remain unknown. Here, reconstitution and characterization of D2R in a supported model membrane in nanometric confinement are reported. D2R is expressed in Chinese hamster ovary (CHO) cells and transferred into the supported model membrane as cell membrane blebs. D2R molecules are reconstituted with an elevated density in the cleft between the substrate and poly(dimethylsiloxane) (PDMS) elastomer. Reconstituted D2R retains the physiological functions, as evaluated from its binding to an antagonist and dimerization lifetime. The transient dimer formation of D2R, similar to the live cell, suggests that it is an innate property that does not depend on the cellular structures such as actin filaments. Although the mechanism of this unique reconstitution process is currently not fully understood, the finding points to a new possibility of using a nanometric space (<100 nm thick) as a platform for reconstituting and studying membrane proteins under the quasi-physiological conditions, which are difficult to be created by other methods.
CRIS-Team Scopus Importer:2021-11-19
Keywords: dopamine D2 receptor; G-protein-coupled receptor; model membrane; nanofluidics; single molecule observation